Ehlers-Danlos syndrome with huge bladder diverticulum in pregnancy – A rare and interesting case report. (July 2020) - Pradhan, Neekita; Shilawant, Jyothi; Akkamahadevi, C.H.; Shivakumar, K.S.; Sundaresh, D.C.
Abstract: Ehlers-Danlos syndrome (EDS) is one of the commonest inheritable connective tissue disorders (CTD) affecting one in 5000 people globally. The incidence of bladder diverticula (BD) is reported to be 1.7% seen more commonly in children without any bladder outlet obstruction. BD are associated with congenital syndromes, namely, EDS. We report a case of huge BD in pregnancy that became symptomatic as the pregnancy progressed to term with urinary retention, recurrent urinary infections and fetal malpresentation. The patient was taken for elective Lower segment cesarean section (LSCS) wherein intra-operative findings of soft abdominal wall, velvety and jelly-like rectus muscle made us suspect connective tissue disorder. A thorough retrospective evaluation of medical history, physical examination along with orthopedic evaluation led to the diagnosis of EDS. To the best of our knowledge, this is the first case report of EDS with huge BD in pregnancy.